(3TQM eHMK GdGSJUMGH ef aQGFO GdCUhd GdeYQha HGdQSGFd ddCfUGQjs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdJYGOd hGdJQGLjM ef cJGH aQGFO GdCUhd, bhdg aj GdJYGOd hGdJQGLjM EfeG CJi HdaX GdeYfi aj GdJYGOd hHdaX GdLeY aj GdJQGLjM dCf GdJYGOd CeQ hGMO hgh YOe hLhO GdeQLM HNdGa GdJQLjM aEfg CeQ eJYOOs
(3BNQgG (B:s
(3BNQgG(B: (3heeG PcQfG, Gj eeG PcQfG ef CLRGA GdJQGLjM aj ZjQ GdCNHGQ ef GdGLeGYGJ GdefbhdI hGdCeQGJ GdXfjI JYQa Mce GdGLeGY Gdefbhd Ch ZjQg ef GdGeGQGJ GdXfjI EPG JYGQVJ eY GdNHQ hCfg jCNP HeG hLO ajg GdeQLM, bhdg dh hLO Cj Cj dh hLO NHQ eYGQV dGLeGY efbhd Chs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs